(untitled) (Journal of Pathology of Nepal, 2019)
Background: Hyperemesis gravidarum is a complex condition characterized by excessive nausea and vomiting during pregnancy. It presents with various symptoms which include disturbed nutrition, electrolyte imbalance, ketosis and extreme weight loss. The objective of this study is to compare serum lipase, amylase and glucose in Hyperemesis gravidarum with non-pregnant women. Materials and methods: A total of 100 subjects among which 50 were nonpregnant women as controls and 50 were women with hyperemesis gravidarum as cases were enrolled in the study. Serum lipase, amylase and glucose levels were estimated in all the subjects. Results: The levels of mean serum lipase were lesser in cases (23.55 ± 4.91U/L) compared to that in controls (25.45 ± 5.97U/L) with p=0.086. However, the levels of mean serum amylase were higher in cases (76.40 ± 33.86 U/L) compared to that in controls (69.66 ± 16.45U/L) with p= 0.210. Serum amylase activity was raised in 8% of the patients whereas the activity of pancreatic lipase was within normal range. Serum glucose levels were lower in cases (84.72 ± 11.28 mg/dl) than that in controls (87.04 ± 10.65 mg/dl) with p=0.293. Conclusions: From this study we conclude that lipase activity was statistically insignificant in hyperemesis gravidarum. Therefore, pancreatic activities were less affected by hyperemesis gravidarum. So, this condition needs further exploration regarding biochemical basis to minimize the risk associated with it.